Occurrence of Parapox Virus in a 3-year-old Cow and the Resulting Lesions in a Milking Calf - Raman, A.; R.Durairajan (The Indian Veterinary Journal, 2026)
Parapox virus, causes Pseudocowpox in dairy cows, a mild infection of the udder and teats. Pseudo cowpox virus (PCPV) wPseudocowpoxas identified in a 3-year-old dairy cow with papule lesions on the surface of the teat and udder. Diagnostic specimens (oral swabs from the adult cow and calf from a dairy farm in Tiruvannamalai) were collected, and the poxvirus DNA was obtained from the teat lesion material. It was confirmed as Pseudocowpox virus by a PCR test, which produced 594 bp of amplicon. The results revealed that cattle were infected with PPV.